Guidelines for an effective design of serious games - Chiara Eva Catalano; Angelo Marco Luccini; Michela Mortara (Serious Games Society, 2014)
There is an increasing awareness about the potential of serious games for education and training in many disciplines. However, research still witnesses a lack of methodologies, guidelines and best practices on how to develop effective serious games and how to integrate them in the actual learning and training processes. The process of integration heavily depends on providing and spreading evidence of the effectiveness of serious games. In this paper we present an overview on the factors that make serious games effective in the perspective of maximizing the learning impact. Such recommendations are the result of an extensive survey of the current proposition of serious games in different application domains.